Pengaruh Budaya Organisasi dan Struktur Organisasi Terhadap Kualitas Sistem Informasi Akuntansi Pemerintah Desa di Kecamatan Kabila Bone Kabupaten Bone Bolango - Mattoasi Mattoasi; Lukman Pakaya; Siti Fajrin Chairunnisa (Economics and Digital Business Review, 2023)
This study aims to determine the effect of organizational culture and organizational structure on the quality of accounting information systems. This type of research used is a quantitative method. The data source used in this research is primary data obtained directly from respondents through questionnaires distributed to village officials in Kabila Bone District, Bone Bolango Regency. The total population in this study was 9 villages using a sampling technique so that the number of samples used was 4 villages. The results of this study show that organizational culture (X1) and organizational structure (X2) partially have a positive and significant effect on the quality of accounting information systems (Y).